Exploring plasticity in the wild: laying date–temperature reaction norms in the common gull Larus canus - Brommer, Jon E (The Royal Society, 2008)
Exploration of causal components of plasticity is important for insight into evolutionary dynamics and an organism's ability to respond to climate change. Among individuals, variation in plasticity can be due to genotype–environment interaction (G×E) or a result from environmental effects associated with an individual. We investigated plasticity for laying date in the common gulls Larus canus, using data collected in Estonia during 37 years (n=11 624 records on 2262 females, with 472 relatives). We used a sliding window approach to find the period in spring during which mean temperature best explained the annual mean laying date. Then, considering the spring temperature as a quantitative description of the environment, we used pedigree information and a random regression animal model to determine the variation in plasticity for the laying date–temperature relationship. We found that individuals differ in the plasticity of laying date (such that there is increased variation among individuals for the laying date in warmer springs), and that approximately 11% of variation in the laying date is heritable, but we found no statistical support for G×E. Plasticity in this species is not constrained by warmer springs.